Phylogeny of Philornis Meinert species (Diptera: Muscidae) - Couri, Márcia Souto; de Carvalho, Claudio José Barros; Löwenberg-Neto, Peter (Zootaxa, 2007)
This study presents a cladistic analysis of the Neotropical Philornis species based on morphological characters of adults and larvae, as well as biological data on larvae. Forty-one species of Philornis were used in the analysis, which was based on a total of 64 characters and included six outgroup taxa, half of which belong to Passeromyia Rodhain & Villeneuve, an Old World genus that shows the same variety of associations with birds as Philornis. Four most parsimonious cladograms (242 steps in length; ci=30; ri=69) were produced. According to the analysis, the genus Philornis is supported by the following synapomorphies (adults): only the pre-scutellar pair of acrostichal postsutural setae developed and setulae on anepimeron present. The resulting phylogenetic hypothesis (strict consensus) shows a basal polytomy that includes the species that traditionally correspond to the “aitkeni-group”. This group is mainly defined by male characters, which are known for only about half of these species. The next clade is divided into two others, the first one supported by the homoplasies: cheek hairs yellow; setulae on anepimeron black on upper half and yellow on lower half and proepimeral hairs yellow. This group traditionally corresponds to the “falsificus-group” and more data on the biology of the species will certainly clarify and/or confirm their relationships. Philornis downsi Dodge & Aitken is the sister group of all the remaining Philornis species. This third clade corresponds to the “angustifrons-group”, defined in this analysis by the following synapomorphies: concave shape of posterior end of puparium and the median width of female frons. These “traditional” groups, the relationships among the species and their evolutionary trends are discussed.